The Influence of Owner Characteristics on the Utilization of Yards in Planned and Unplanned Settlements - Sutrisno, Alfred J; Astuti, Ani P (Universitas Pattimura, 2023)
Yard is important for the community of Salatiga City. Salatiga City has two types of settlements, namely planned and unplanned settlements. The utilization of yards in both types of settlements differs. Therefore, this study aimed to examine the influence of yard owner characteristics on yard utilization, which was assessed by the visual condition of yards in planned and unplanned settlements. Yard owner characteristics were assessed by length of stay, age, and occupation. The sample selection method used was purposive sampling, with a total of 35 respondents. 10 respondents were from planned settlements and 25 respondents from unplanned settlements. The data analysis method used was Scenic Beauty Estimation (SBE), which was used to assess visual quality. Visual quality was divided into three categories: low, medium, and high. Subsequently, the Kruskall Wallis test was used to examine the influence of owner characteristics on yard utilization. The results showed that out of 10 yards in planned settlements, two yards were in the high category, five yards in the medium category, and three yards in the low category. Meanwhile, in unplanned settlements, out of 25 yards, 11 yards were in the high category, nine yards in the medium category, and five yards in the low category. The owner characteristic that influenced yard utilization was the owner occupation, which was seen from the Asymp. Sig. value <0.05, which was 0.049.